How distributed processing produces false negatives in voxel-based lesion-deficit analyses. (1st July 2018) - Gajardo-Vidal, Andrea; Lorca-Puls, Diego L.; Crinion, Jennifer T.; White, Jitrachote; Seghier, Mohamed L.; Leff, Alex P.; Hope, Thomas M.H.; Ludersdorfer, Philipp; Green, David W.; Bowman, Howard; Price, Cathy J.
Abstract: In this study, we hypothesized that if the same deficit can be caused by damage to one or another part of a distributed neural system, then voxel-based analyses might miss critical lesion sites because preservation of each site will not be consistently associated with preserved function. The first part of our investigation used voxel-based multiple regression analyses of data from 359 right-handed stroke survivors to identify brain regions where lesion load is associated with picture naming abilities after factoring out variance related to object recognition, semantics and speech articulation so as to focus on deficits arising at the word retrieval level. A highly significant lesion-deficit relationship was identified in left temporal and frontal/premotor regions. Post-hoc analyses showed that damage to either of these sites caused the deficit of interest in less than half the affected patients (76/162 = 47%). After excluding all patients with damage to one or both of the identified regions, our second analysis revealed a new region, in the anterior part of the left putamen, which had not been previously detected because many patients had the deficit of interest after temporal or frontal damage that preserved the left putamen. The results illustrate how (i) false negative results arise when the same deficit can be caused by different lesion sites; (ii) some of the missed effects can be unveiled by adopting an iterative approach that systematically excludes patients with lesions to the areas identified in previous analyses, (iii) statistically significant voxel-based lesion-deficit mappings can be driven by a subset of patients; (iv) focal lesions to the identified regions are needed to determine whether the deficit of interest is the consequence of focal damage or much more extensive damage that includes the identified region; and, finally, (v) univariate voxel-based lesion-deficit mappings cannot, in isolation, be used to predict outcome in other patients. Highlights: Post-hoc analyses of results from voxel-based lesion-deficit analyses are reported. The effects of different lesion sites cancel each other out when all data are pooled. Removing patients with one lesion site can reveal other critical lesion sites. Our findings highlight the need for multivariate lesion-deficit analyses.